Social life cycle assessment of different packaging waste collection system - ÇİFTÇİOĞLU, GÖKÇEN ALEV (ELSEVIER SCIENCE BV, 2017)
Recycling is one of the most preferable tools of the sustainability concept considering its economic benefits and environmental effects. However, environmental and economic benefits are not always enough to accomplish a sustainable life concept. Social impacts, which basically focus on issues such as the well-being of humans, should be also considered. Regarding this concept; in this study we aimed to analyze the social impacts of different packaging waste management systems. In this context, we proposed eleven scenarios, which consisted of hypothetical formal and informal collection scenarios. All these scenarios were compared with the currently applied collection system in Istanbul, Turkey. The social analysis was conducted by using Life Cycle Assessment methodology. The results of this study showed that existing system and informal collection scenarios had socially fewer score than the formal scenarios in almost all impacts. Between the formal collection systems, there were slight differences caused by especially working conditions and socio-economic repercussion. However, formal collection scenarios showed more negative social impacts than formal-informal system integration. The result of this study showed that it was crucial to consider an amelioration on the informal collection system. In the integrated scenario (S11), some of the critical subcategories were idealized and improved taking into consideration to the long term modification issues. Although we couldn't minimize all negative social impacts; it was obvious that this scenario was still the best option. Finally, we may conclude that application of an ameliorated informal collection system would be socially more beneficial than formal and informal collection systems.
Keywords: Packaging waste; Social analysis; Social life cycle assessment; Formal and informal collection; IMPACT ASSESSMENT; ENVIRONMENTAL ASSESSMENT; RECYCLING SYSTEMS; ENERGY RECOVERY; LCA; METHODOLOGY